Officers of the 2nd artillery-group "S̆koda" and Spanish children at a fête at Abelda. Place of persons on back. Copied from collection Museum für Deutsche Geschichte (1937)
Officers of the 2nd artillery-group "S̆koda" and Spanish children at a fête at Abelda. Place of persons on back. Copied from collection Museum für Deutsche Geschichte.